THE EFFECT OF TAX LITERACY AND CORETAX DIGITALIZATION PERCEPTION ON FINAL INCOME TAX COMPLIANCE INTENTIONS OF MSMEs - Achmad Hilmy Syarifudin; Alvito Putra Aldinova; Lira Azh Zhahra Salim; Sabrina Natasha Rachmaputri; Sekar Andiningtyas Putri (JAT : Journal Of Accounting and Tax, 2025)
This study examines the influence of tax literacy and perceptions of administrative digitalization through Coretax on the tax compliance intentions of Micro, Small, and Medium Enterprises (MSMEs) in the Jakarta and Depok regions, Indonesia. This study uses a quantitative approach with a survey method. The analysis technique used is multiple linear regression with the help of SPSS version 26 software. The results show that tax literacy and perceptions of administrative digitalization through Coretax have a positive and significant effect on tax compliance intentions. The digitalization perception variable has a coefficient of 0.514 (p < 0.01), while tax literacy has a coefficient of 0.308 (p < 0.05), so both are proven to increase the compliance intentions of informal sector MSMEs in the 0.5% Final Income Tax scheme. The final regression model has an Adjusted R² Square value of 0.450, which means that 45% of the variation in tax compliance intentions can be explained by tax literacy, perceptions of administrative digitalization through Coretax, and the control variables used. This research is expected to be a policy basis for the government and the Directorate General of Taxes in expanding the socialization of tax literacy and optimizing the use of Coretax, especially for MSMEs, to encourage sustainable tax compliance.